Maximising trichiasis surgery success (MTSS) trial: rationale and design of a randomised controlled trial to improve trachomatous trichiasis surgical outcomes - Beatriz Munoz; Emily W Gower; Belay Bayissasse; Kristin M Sullivan; Shannath L Merbs; Alexander Keil; Alemayehu Sisay; Alison Singer (BMJ Open)
Introduction Trachomatous trichiasis (TT) is a condition in which the eyelid turns inward and eyelashes abrade the front part of the eye. To prevent eventual blindness, surgery is recommended. Two surgical procedures are commonly used, bilamellar tarsal rotation (BLTR) and posterior lamellar tarsal rotation (PLTR). Evidence suggests that incision height and surgery type may affect the risk of postoperative TT (PTT) and other surgical outcomes. However, these studies have not prospectively compared the impact of incision height on surgical outcomes.Methods and analysis Maximising trichiasis surgery Success (MTSS) is a three-arm, randomised clinical trial being conducted in Ethiopia. Participants will be randomly assigned on a 1:1:1 basis to BLTR with a 3 mm incision height, BLTR with a 5 mm incision height, or PLTR 3 mm incision height. Patients are eligible for the trial if they have previously unoperated upper eyelid TT. Follow-up visits will be conducted by trained eye examiners at 1 day, 2 weeks, 6 weeks and 12 months after surgery. The primary outcome is incident PTT within 1 year following surgery. Logistic regression will be used in an intention-to-treat analysis to assess outcome incidence by surgical approach.Ethics and dissemination The University of North Carolina and Johns Hopkins School of Medicine institution review boards, Ethiopian National Research Ethics Review Committee and Ethiopian Food, Medicine, Healthcare and Administration and Control Authority provided ethics approval for the trial. On completion, trial results will be disseminated at local and international meetings and in peer-reviewed journals.Trial registration number NCT03100747.